Proposta de roteirização para o transporte público universitário de Araguaína, TO. - Ferreira, Marilene dos Santos (Universidade Federal do Tocantins, 2023)
Collective public transport facilitates the movement of people and helps the population to carry out daily activities and contributes to the agility and speed of traffic. However, it is observed that the services offered do not always meet the expectations and needs of passengers. In view of this low efficiency of public transport, this work seeks to model a new bus route aimed at university students in the city of Araguaína, Tocantins, contributing to the improvement of the service offered. For this purpose, the Traveling Salesman Problem (TSP) was used, which seeks to find the lowest cost circuit that connects several points, passing through each point only once and returning to the origin. By limiting itself to eight Higher Education Institutions (HEI), it was possible to build an optimal route with 26.4 km and an ideal journey time of approximately 44 minutes. The effective implementation of this route will provide students with an alternative to the existing fragmented routes, allowing for greater integration between the HEI and reduced travel time between them, in addition to connecting several central points in the city.